Efektivitas Pemupukan Urea Padat dan Cair Melalui Biopori pada Pertumbuhan Morfologi Kelapa Sawit Menghasilkan Umur Lima Tahun - Ratih Ratih Rahhutami; Danie Indra Yama; Tonny Iskandar (JURNAL CITRA WIDYA EDUKASI, 2019)
The plantation of oil palm add urea fertilizer to meet the needs of plant nitrogen, but urea fertilizer is very easy to dissapear and can not be absorbed by plants. This research aims to determine the response of morphology on five years old mature oil palm to two ways of application urea fertilizer and to get the most effective way application urea fertilizer for growth of five years old mature oil palm. This research was conducted at Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Mekar Sari Village, Subang, Jawa Barat in July – December 2017.. The experiment was arranged in a completely randomized block design with one factor. There are two treatments: urea fertilizer not thawed (P1) and urea fertilizer thawed (P2). Each treatments were two replications, and each replications consisted of 2 sample plants so the total unit of experiments were 8 plants. Data were analized with analysis of variance with α 5 %, If there is a significant treatment effect, the further analysis using LSD (Least Significant Differences). The result showed that the fertilization of solid and liquid urea through biopories did not significantly affect for all variabels from the beginning to the end of the research and the application of solid and liquid urea fertilizer showed the same effectiveness for growth of five years old mature oil palm.